Alternative media & mainstream politics: The case of mediated political fusion - Atkinson, Joshua D.; McWan, Blessy; White, Jewel; Hoque, Rafsanul (Taylor and Francis, 2024)
This article was published in The Digital Journalism [©2022 Rights managed by Taylor & Francis ] and the definite version is available at: https://doi.org/10.1080/21670811.2022.2066010 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/21670811.2022.2066010